The Potential of Flavonoids and Flavonoid Metabolites in the Treatment of Neurodegenerative Pathology in Disorders of Cognitive Decline - James Melrose (MDPI AG, 2023)
Flavonoids are a biodiverse family of dietary compounds that have antioxidant, anti-inflammatory, antiviral, and antibacterial cell protective profiles. They have received considerable attention as potential therapeutic agents in biomedicine and have been widely used in traditional complimentary medicine for generations. Such complimentary medical herbal formulations are extremely complex mixtures of many pharmacologically active compounds that provide a therapeutic outcome through a network pharmacological effects of considerable complexity. Methods are emerging to determine the active components used in complimentary medicine and their therapeutic targets and to decipher the complexities of how network pharmacology provides such therapeutic effects. The gut microbiome has important roles to play in the generation of bioactive flavonoid metabolites retaining or exceeding the antioxidative and anti-inflammatory properties of the intact flavonoid and, in some cases, new antitumor and antineurodegenerative bioactivities. Certain food items have been identified with high prebiotic profiles suggesting that neutraceutical supplementation may be beneficially employed to preserve a healthy population of bacterial symbiont species and minimize the establishment of harmful pathogenic organisms. Gut health is an important consideration effecting the overall health and wellbeing of linked organ systems. Bioconversion of dietary flavonoid components in the gut generates therapeutic metabolites that can also be transported by the vagus nerve and systemic circulation to brain cell populations to exert a beneficial effect. This is particularly important in a number of neurological disorders (autism, bipolar disorder, AD, PD) characterized by effects on moods, resulting in depression and anxiety, impaired motor function, and long-term cognitive decline. Native flavonoids have many beneficial properties in the alleviation of inflammation in tissues, however, concerns have been raised that therapeutic levels of flavonoids may not be achieved, thus allowing them to display optimal therapeutic effects. Dietary manipulation and vagal stimulation have both yielded beneficial responses in the treatment of autism spectrum disorders, depression, and anxiety, establishing the vagal nerve as a route of communication in the gut-brain axis with established roles in disease intervention. While a number of native flavonoids are beneficial in the treatment of neurological disorders and are known to penetrate the blood-brain barrier, microbiome-generated flavonoid metabolites (e.g., protocatechuic acid, urolithins, γ-valerolactones), which retain the antioxidant and anti-inflammatory potency of the native flavonoid in addition to bioactive properties that promote mitochondrial health and cerebrovascular microcapillary function, should also be considered as potential biotherapeutic agents. Studies are warranted to experimentally examine the efficacy of flavonoid metabolites directly, as they emerge as novel therapeutic options.